Fate and transport of phosphorus‐containing land‐applied swine slurry in a karst watershed. Issue 1 (31st August 2020) - Sharpley, A. N.; Daniels, M. B.; Brye, K. R.; VanDevender, K.; Burke, J.; Berry, L. G.; Webb, P.
Abstract: Phosphorus distribution in pasture soils underlain with karst geology was determined on a 0.10‐ha grid in 2014, 2016, and 2018. Two fields (Fields 1 and 12) received swine slurry from a concentrated animal feeding operation, whereas another (Field 5) received mineral fertilizer. All fields were grazed by cattle and periodically hayed. Mean Mehlich‐3 extractable P in the top 10 cm increased ( p  ≤ .05 level) for Fields 1 (59–91 mg kg −1 ) and 12 (63–122 mg kg −1 ) between 2014 and 2018, with little change for Field 5 (45–47 mg kg −1 ). Over the 5‐yr monitoring period, P and N runoff averaged a respective 1.0 and 2.4 kg ha −1  yr −1 from Fields 1 and 12 or 1.4 and 2.5% of P and N applied in swine slurry. Field 5 P and N runoff averaged a respective 1.9 and 2.8 kg ha −1  yr −1 or 6.6 and 4.4% of that applied as mineral fertilizer. Findings confirmed that long‐term application of P, as fertilizer or manure, in excess of pasture uptake, result in a rapid accumulation of P near the soil surface, and thus, increase nutrient loss via surface runoff. Mehlich‐3 P increased in the top 10 cm of soil (143–255 mg kg −1 ) in edge‐of‐field buffer zones of 30 m on Fields 1 and 12, where no manure was applied. This illustrates the complexity of cattle grazing areas as additional nutrient sources that must be managed to minimize off‐site nutrient transport that are particularly important in karst watersheds.